Prominence observations with ALMA - Heinzel, Petr; Bárta, Miroslav; Gunár, Stanislav; Labrosse, Nicolas; Vial, Jean-Claude (Frontiers in Astronomy and Space Sciences, 2022)
We review past prominence observations in the mm/sub-mm radio domain and summarize the basic physics behind the formation of such continua under the prominence conditions. Prior to ALMA observations, simulations of the prominence/filament visibility in mm/sub-mm bands were performed using specific models and assumptions and we review this effort here. A core part of the review is the description and analysis of the first ALMA observations of a quiescent prominence, focusing on various physical as well as geometrical (like the importance of the PoS filling factor) aspects. It is first time when the prominence was observed in the mm domain with a spatial resolution as high as 1-2 arcsec, comparable to ground-based coronagraphic observations in the hydrogen H$α$ line, and we demonstrate why the fine structures in both ALMA Band 3 and H$α$ images are quite similar. Finally, we briefly discuss future prospects of ALMA prominence observations, to be coordinated with optical and UV spectra and images.